A cultural biography of an acclaimed Queen of Xhosa music, Madosini Manqineni, and her contributions to Xhosa cultural music - Plaatjies, Mzikantu Zungula (College of Music, 2024)
The main objective of this study is a musical ethnography on Madosini Manqineni, a prominent individual in African cultural music today, with an established reputation abroad, but who has not yet been given any attention in scholarship. This study was motivated by my great admiration and respect for Madosini, who is recognized as a "specialist musician", a notion that did not exist in pre-colonial times. In this study I am concerned with biography, which also needs some historical data. My writing comes from my position as a professional musician who was also a long-term student of Madosini. Although certain areas of her life are not fully available to me, I set out to explore how and why she became a professional musician, the social circumstances which encouraged her to cultivate her music, first in the customary way, which later became more individual and personal. Chapter 1 places the subject in her historical and cultural background, with a summary of main events in Mpondomise history and Madosini's family predecessors of the Dosini clan. Chapter 2 looks at events in Madosini's childhood which laid the foundation of her musical career, experiences of sets of customs, social and musical, in a rural/traditional environment; restrictions of a physical defect which encouraged concentration on self-accompanied song, and song stories. Chapter 3 concerns Madosini's handling of the intsomi tradition, but also contains critical debate on intsomi as 'folk tale' as an 'oral literature', with reference to earlier scholars; the Xhosa approach to intsomi and an example of such by Madosini, in the Xhosa language, with English translation. Chapter 4 looks at Madosini as a teacher, composer and musical specialist, and contains a detailed account of my experiences as her student; Madosini's idiosyncratic procedures in bow performance practice, in song composition, and their impact on my career as a professional musician. Chapter 5 provides a summary of the preceding chapters and a commentary on Madosini's contributions to Xhosa music. The dissertation ends with an epilogue, paying tribute to Madosini, whose achievements continue to encourage young musicians to promote cultural music and to take new directions with it, thereby ensuring its continuity down the generations.